Reproductive Health Literacy Enhancement through School-Based Health Education for Adolescents - Septiana, Septiana; Asidi, Juhdi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to see the influence of health education about reproductive health on students' level of knowledge. Methodology: The research sample used was 24 people using a convenience sampling technique. The method used was a pre-experimental design with a one-group pre-test post-test design. Data collection used a questionnaire as a research instrument. The data analysis technique used was the Wilcoxon test. Main Findings: The results of the study showed that students' knowledge before receiving health education had an average value of 81.9%, and after receiving health education it increased to 86.3%. The results of the hypothesis test with an alpha error rate of 0.05 obtained a p value > 0.05, meaning there was no significant difference in adolescents' knowledge before and after receiving health education. Novelty/Originality of this study: This research presents a novel approach by in-depth examining the influence of health education on improving adolescents' knowledge of reproductive health using a contextual and interactive educational approach. The focus on adolescents in the digital age makes these findings crucial for developing more relevant, responsive, and sustainable school intervention strategies.